Nitrate pollution of groundwater long exceeding trigger value: Fertilization practices require more transparency and oversight - Greta Sundermann; Nicole Wägner; Astrid Cullmann; Christian R. von Hirschhausen; Claudia Kemfert (DIW Weekly Report, 2020)
For many years now, nitrate concentrations have exceeded the trigger value of 50 milligrams per liter at nearly one-fifth of the groundwater sampling sites in Germany. Apart from impairing the ecosystem by, for example, causing eutrophication of water bodies, nitrate-polluted drinking water also damages human health; it is suspected to cause cancer. Econometric calculations using current data confirm the correlation established in the literature between nitrate pollution and intensive agriculture. Federal states with intensive agriculture, such as Saxony, Lower Saxony, Schleswig-Holstein, Rhineland-Palatinate, and Saxony-Anhalt, are particularly affected by nitrate pollution. While the German federal and state governments revised the fertilizer ordinance in 2017, it remains insufficient to effectively combat nitrate pollution of groundwater. As a result, the European Union brought proceedings against Germany for non-compliance, threatening fines in the millions of euros. The Fertilizer Ordinance to be adopted in 2020 must ensure compliance with the trigger value for nitrate pollution. Progress has already been made by introducing state-specific regulations and increasing reporting obligations on nutrient inputs. Nevertheless, the effectiveness of these measures should be reviewed closely and, if necessary, supplemented with additional regulatory measures.
Keywords: Q15; Q53; Q58; 330; water pollution; nitrate concentration; water prices